2006
DOI: 10.1111/j.1440-1681.2006.04336.x
|View full text |Cite
|
Sign up to set email alerts
|

PROTECTIVE EFFECTS OF l‐CARNITINE ON MYOGLOBINURIC ACUTE RENAL FAILURE IN RATS

Abstract: 1. Muscle injury (rhabdomyolysis) is one of the causes of acute renal failure (ARF). Iron, free radicals and nitric oxide (NO) play a critical role in the pathogenesis of glycerol-induced myoglobinuric ARF. L-Carnitine is an anti-oxidant and prevents the accumulation of end-products of lipid peroxidation. Therefore, the aim of the present study was to investigate the effects of L-carnitine on myoglobinuric ARF induced by intramuscular (i.m.) hypertonic glycerol injection. 2. Sprague-Dawley rats were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 36 publications
6
52
0
Order By: Relevance
“…The protective role of nitric oxide (NO) in different models of renal failure has been documented [136], including glycerol-induced renal failure [137] and nephrolithiasis induced by ethylene glycol [138]. These studies have demonstrated that levels of NO are decreased in glycerol-induced renal failure and different agents have shown to produce renoprotection by increasing the NO production [120].…”
Section: Pomegranate (Punica Granatum L)mentioning
confidence: 99%
“…The protective role of nitric oxide (NO) in different models of renal failure has been documented [136], including glycerol-induced renal failure [137] and nephrolithiasis induced by ethylene glycol [138]. These studies have demonstrated that levels of NO are decreased in glycerol-induced renal failure and different agents have shown to produce renoprotection by increasing the NO production [120].…”
Section: Pomegranate (Punica Granatum L)mentioning
confidence: 99%
“…The effects of LC on the metabolism of tissues in organs such as the heart [15], brain [16], and liver [13] have been studied widely. Current reports suggest that LC may play a significant role in balancing antioxidative systems and has an antiperoxidative effect on some tissues [17,18]. The aim of this study was to investigate possible protective effects of exogenous LC supplementation on CDDP-induced oxidative organ injuries, and its effects on the levels of antioxidant enzymes and lipid peroxidation, as well as histological changes.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, carnitine also prevents increase in MDA levels in IR damage in several organs and in renal damage caused by several agents. 23,24,28,29,32 According to all these findings, it is possible to say carnitine prevents lipid peroxidation in infrarenal AIR models in doserelated fashion and this effect of carnitine also contributes in the prevention of possible renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27] Carnitine also decreases renal damage developed because of several agents. [28][29][30][31][32] Although carnitine has been shown to decrease lung damage in infrarenal AIR models, effect of carnitine on renal damage in this model has not been studied. 33 This study was designed to investigate the effect of carnitine, an antioxidant agent, in rat models in decreasing IR damage developing in kidneys following infrarenal aortic occlusion-reperfusion and in preventing kidneys from this kind of damage.…”
Section: Introductionmentioning
confidence: 99%